Economic Impact of a Rotavirus Vaccine in Brazil - Constenla, Dagna O; Linhares, Alexandre C; Rheingans, Richard D; Antil, Lynn R; Waldman, Eliseu A; da Silva, Luiz J (Journal of Health, Population and Nutrition, 2009)
<!--[if gte mso 9]> Normal 0 false false false MicrosoftInternetExplorer4 <![endif]--><!--[if gte mso 9]> <![endif]--><!--[if !mso]> <![endif]--> <!--[if gte mso 10]> <![endif]--> The study was done to evaluate the cost-effectiveness of a national rotavirus vaccination programme in Brazilian children from the healthcare system perspective. A hypothetical annual birth-cohort was folÂlowed for a five-year period. Published and national administrative data were incorporated into a model to quantify the consequences of vaccination versus no vaccination. Main outcome measures included the reduction in disease burden, lives saved, and disability-adjusted life-years (DALYs) averted. A rotavirus vacÂcination programme in Brazil would prevent an estimated 1,804 deaths associated with gastroenteritis due to rotavirus, 91,127 hospitalizations, and 550,198 outpatient visits. Vaccination is likely to reduce 76% of the overall healthcare burden of rotavirus-associated gastroenteritis in Brazil. At a vaccine price of US$ 7-8 per dose, the cost-effectiveness ratio would be US$ 643 per DALY averted. Rotavirus vaccination can reduce the burden of gastroenteritis due to rotavirus at a reasonable cost-effectiveness ratio. Key words: Costs and cost analysis; Diarrhoea, Infantile; Gastroenteritis; Morbidity; Rotavirus; Rotavirus vaccines; Vaccination; Brazil doi:10.3329/jhpn.v26i4.1880 J Health Popul Nutr 2008 Dec:26(4):388-396